Weeds associated with garlic crops in southern Nuevo León - González-Delgado, Marisol; Manzanares-Miranda, Nelson; Gómez-Tienda, Paola Azereth; Rocha-Domínguez, Luís (Revista Mexicana de Ciencias Agrícolas, 2025)
The state of Nuevo León ranks fifth in the national production of garlic with a production of 3 044 t and an average yield of 8.8 t ha-1. Garlic crops are important to the south of the state for more than 150 producers. One of the main problems is the presence of weed plants. The purpose of this work was to record the main species of weeds present in garlic crops in the locality of La Ascensión, Aramberri, Nuevo León, Mexico. The size of the plot was 16 m2, the species found were recorded, and the identity and their synonyms were verified. For the ecological characterization, the height, cover, and diameter of the individuals found in each of the sampling plots were evaluated. For each species, the following structural variables were calculated: abundance, dominance, frequency and importance value. A total of 21 species were found, which are cataloged in 12 families, among which Asteraceae (6) and Brassicaceae (3) predominate. The cluster analysis showed that there is similarity in terms of the number of individuals and species per farm in three of the units. The species Argemone grandiflora and Centaurea rothrockii presented the highest abundance, whereas the highest dominance and importance value is held by Argemone grandiflora.
Keywords: Argemone grandiflora; competition; cultural practices; garlic; weeds